Biochemical Polymorphism in Newzealand White X Chinchilla Rabbit Crosses (2017)
The study evaluated diversity within New Zealand white and Chinchilla rabbit crosses using four structural protein loci: Hemoglobin (Hb), Albumin (Alb), Transferin (Tf) and Carbonic anhydrase (CA). Blood (4mls) was sampled from a total of 49 rabbits through ocular venipuncture. The samples collected were analysed using cellulose acetate electrophoresis to estimate the genetic variability within the populations. The degree of heterozygosity, deviation from Hardy Weinberg's Equilibrium (HWE), F , and F values were estimated. All four proteins IS ST loci studied were found to be polymorphic. CA and Alb produced two codominant alleles which controlled three different genotypes. While the two observed codominant alleles in Hb and Tf controlled two genotypes. The haemoglobin locus had the highest heterozygosity value (0.87) while the lowest value (0.53) was recorded at the Albumin locus. Significant deviation from Hardy-Weinberg equilibrium (P < 0.05) was observed at Hb and Tf loci while CA and Alb loci were found to conform with Hardy-Weinberg equilibrium (p > 0.05). Negative F values IS were obtained for all the studied loci indicating the deficiency of homozygotes in the population and that mates were less related in comparison to the average relationship of the population. The results obtained could serve as a reference point in the genetic improvement of the rabbit genetic resource.